3D coupled field in a transversely isotropic magneto-electro-elastic half space punched by an elliptic indenter. (February 2015) - Li, X.-Y.; Wu, F.; Jin, X.; Chen, W.-Q.
Abstract: The present paper is concerned with three-dimensional (3D) coupled field in a transversely isotropic magneto-electro-elastic half space punched by a rigid flat-ended elliptic indenter. Closed form solutions and corresponding numerical results are presented in this work, in a systematic manner. The material in question is transversely isotropic with the axis of symmetry normal to the surface of the half space. The indenter is assumed to be either electrically and magnetically conducting or insulating. Corresponding boundary integral equations (BIEs), to indenter with different magneto-electric properties, are solved by virtue of the method of generalized potential theory. For all four physical cases, corresponding coupled magneto-electro-elastic fields in the half space are obtained. The present analytical solutions indicate that the indentation forces and stiffness may be written as intrinsic combinations of a physical factor and a geometrical factor. The present study is an extension of the previous work on circular punch, and may find applications in guiding future indentation experiments. Abstract : Highlights: 3D coupled fields of MEE contact are derived in explicit closed-form solution. 4 types of mixed BIEs are formulated for multi-physics combinations. SIFs for MEE contact singularity are determined in explicit expressions. Contact behavior exhibits intrinsic property of geometric and physical factors. Numerical analyses of MEE contact are systematically performed.